A Comparison of COVID-19 Stigma and AIDS Stigma During the COVID-19 Pandemic: A Cross-Sectional Study in China - Manyun Li (Frontiers Media S.A., 2021)
Objective: To understand the current situation of stigmatizing attitudes toward Coronavirus Disease 2019 (COVID-19) in China and compare it with acquired immunodeficiency syndrome (AIDS).Methods: Convenient sampling and vignette-based methods were used to recruit participants on WeChat. A demographic form and adopted stigma scale were used to collect participants' demographic information and stigmatizing attitudes toward COVID-19 and AIDS.Results: A total of 13,994 questionnaires were included in this study. A high portion of participants tend to avoid contact with individuals affected with COVID-19 (74.3%) or AIDS (59.0%), as well as their family members (70.4% for COVID-19 and 47.9% for AIDS). About half of the participants agreed that affected persons could not only cause problems to their own family but also have adverse effects on others (59.6% and 55.6% for COVID-19, 56.9 and 47.0% for AIDS). The agreements with statements about perceived stigma were similar but slightly higher than those about personal stigma in both COVID-19 and AIDS. Participants' agreements with all statements regarding personal and perceived stigma attitudes between COVID-19 and AIDS were all statistically significant (p < 0.001). Participants obtained COVID-19-related information mainly from social media (91.3%) and newspaper or television (77.1%) during the epidemic, and 61.0% of them thought information from newspapers or television was the most reliable.Conclusion: Several similarities and differences of people's attitude toward COVID-19 and AIDS were found. Avoidance, blame, and secondary discrimination to diagnosed persons and their surrounding persons were the main representations of COVID-19-related stigma. Stigma of COVID-19 had less moral link but more public panic. Experience from HIV-related stigma reduction and prevention can be applied to reduce COVID-19-related stigma.